The Road from Westray: A Predictable Path to Disaster? - Tucker, Eric (Acadiensis, 1998)
Discusses "The Westray Story" (Report of the Westray Mine Public Inquiry, Justice K. Peter Richard, Commissioner, 1997) that made scathing findings regarding the operation of the short-lived mine and the government's failure to regulate it properly.